A circular economy approach: A new formulation based on a lemon peel medium activated with lactobacilli for sustainable control of post-harvest fungal rots in fresh citrus fruit - Mario Riolo; Ana Moreno Villena; Jorge Calpe; Carlos Luz; Giuseppe Meca; Nunzio Tuccitto; Santa Olga Cacciola (Biological Control)
The aim of the study was to develop an effective bio-formulation for preventing post-harvest fungal rots in fresh citrus fruit through a multi-step process that includes isolation and characterization of lactic acid bacteria (LABs) from citrus fruit peel, selection of LAB strains with high antifungal activity, chemical characterization of cell free supernatants (CFS), formulation of a lemon peel powdery-based medium (LM) activated with LAB fermentates, chemical characterization of fermented LM, and evaluation of the efficacy of the new bio-formulation against blue mold. Thirteen LABs were recovered from the rind of citrus fruit and identified by the peptide mass fingerprinting method. The antifungal activity of LABs, isolated from citrus fruit, as well as cell free supernatants (CFSs), obtained from their liquid cultures, was tested against diverse plant pathogenic fungi and oomycetes, using the dual-culture overlay and the diffusion agar assays, respectively. Two isolates designated as N3B2 and M2B2, both identified as Lactiplantibacillus plantarum, were selected among the others for their relevant antifungal activity. Both isolates showed a broad spectrum antagonistic activity comprising also major postharvest pathogens of citrus fruit, such as Penicillium digitatum and P. italicum, the causal agents of green and blue moulds, respectively, Alternaria alternata, Colletotrichum gloeosporioides, C. karsti, Phytophthora citrophthora and Ph. nicotianae. The N3B2 and M2B2 isolates were used as starter cultures to ferment a lemon peel powder medium enriched with a nutrient water solution (LM). The two formulations obtained by fermenting LM with the N3B2 and M2B2 isolates showed a strong in vitro inhibitory activity on the same broad range of pathogens used in the preliminary screening of LABs. Moreover, the two LM-based formulations reduced the severity of blue mold infection and inhibited the sporulation of P. italicum on artificially inoculated lemon fruit. The chemical analysis of LM-based bioformulations revealed their antifungal activity was very probably due to the LAB-derived acidic components, including lactic, acetic, DL-3-phenyllactic, 3-4-dihydroxyhydrocinnamic, salicylic acid vanillic acids. These innovative LM-based bioformulations activated with LAB-derived antifungal compounds will be exploited as edible and biodegradable fruit coatings to prolong the shelf-life and prevent post-harvest rots of fresh citrus fruit.